Assessment of the potential for energy recovery in a sugar cane mill - Jorge Guevara Rodríguez; Juan Pedro Henández Touset; Lirianet Fuentes Ramírez (ITEGAM-JETIA)
One of the problems identified in the sugar industry is the poor management of science and innovation. This paper aims to identify potential energy and water savings and opportunities to improve thermal efficiency in a sugar cane mill using energy analysis and heat integration methods. Methods of energy analysis and pinch analysis are applied using Aspen Energy Analyzer. The establishment of 10 energy performance indicators, which are not currently reported for this industry, will help to define an energy baseline and systematically measure efficiency in the industry. The current hot and cold supply requirements are not met for a minimum allowable temperature difference of 10°C. The design of the heat exchanger network allows 52.23% of the maximum recoverable energy to be recovered.   There is a high excess of the current hot supply duty over the minimum hot duty, behaviour associated with the data extraction system. This study will allow us to continue the research with new heat exchangers and full inter-plant integration.